Gut microbiome features associated with liver fibrosis in Hispanics, a population at high risk for fatty liver disease. Issue 4 (13th December 2021) - Kwan, Suet‐Ying; Jiao, Jingjing; Joon, Aron; Wei, Peng; Petty, Lauren E.; Below, Jennifer E.; Daniel, Carrie R.; Wu, Xiaogang; Zhang, Jianhua; Jenq, Robert R.; Futreal, P. Andrew; Hawk, Ernest T.; et al.
Abstract: Background and Aims: Hispanics are disproportionately affected by NAFLD, liver fibrosis, cirrhosis, and HCC. Preventive strategies and noninvasive means to identify those in this population at high risk for liver fibrosis, are urgently needed. We aimed to characterize the gut microbiome signatures and related biological functions associated with liver fibrosis in Hispanics and identify environmental and genetic factors affecting them. Approach and Results: Subjects of the population‐based Cameron County Hispanic Cohort (CCHC; n = 217) were screened by vibration‐controlled transient elastography (FibroScan). Among them, 144 (66.7%) had steatosis and 28 (13.0%) had liver fibrosis. The gut microbiome of subjects with liver fibrosis was enriched with immunogenic commensals (e.g., Prevotella copri, Holdemanella, Clostridiaceae 1) and depleted of Bacteroides caccae, Parabacteroides distasonis, Enterobacter, and Marinifilaceae. The liver fibrosis‐associated metagenome was characterized by changes in the urea cycle, L‐citrulline biosynthesis and creatinine degradation pathways, and altered synthesis of B vitamins and lipoic acid. These metagenomic changes strongly correlated with the depletion of Parabacteroides distasonis and enrichment of Prevotella and Holdemanella . Liver fibrosis was also associated with depletion of bacterial pathways related to L‐fucose biosynthesis. Alcohol consumption, even moderate, was associated with high Prevotella abundance. The single‐nucleotide polymorphisms rs3769502 and rs7573751 in the NCK adaptor protein 2 ( NCK2 ) gene positively associated with high Prevotella abundance. Conclusion: Hispanics with liver fibrosis display microbiome profiles and associated functional changes that may promote oxidative stress and a proinflammatory environment. These microbiome signatures, together with NCK2 polymorphisms, may have utility in risk modeling and disease prevention in this high‐risk population. Abstract :